Women's modern contraceptive use in sub-Saharan Africa: does men's involvement matter? - Shireen Assaf; Lwendo Moonzwe Davis (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Men's involvement in family planning can play an important role in improving the use of modern contraceptives. Several studies have shown that family planning interventions that involve men have resulted in positive outcomes. However, these studies are mainly case-control studies with a specific focus area. This paper used data from men's responses in Demographic and Health Surveys (DHS) in 27 sub-Saharan African countries to study whether there is an association between men's involvement and modern contraceptive use using nationally represented cross-sectional data. # Methods For the analysis, data on men's involvement was linked with information from women's survey responses on their modern contraceptive use. The objective was to learn whether men's involvement, defined as having correct knowledge, positive attitudes, and supportive behaviors in family planning has an association increased modern contraceptive use in their partners/wives. Women's and men's education level was also examined. Adjusted logistic regression models for modern contraceptive use were fit for each main independent variable along with control variables. # Results Although in general few countries exhibited significant findings, the analysis found that the most significant findings were for the behavior of men discussing family planning with a health care worker. In addition, countries that had a modern contraceptive rate below or equal to 20% had more significant findings than countries that had a modern contraceptive rate of above 20%. # Conclusions Men's behavior was a stronger predictor of women's contraceptive use compared to their knowledge or attitudes. Findings suggest that interventions in countries will low contraceptive could be more effective. The main limitation of the analysis was the cross-sectional nature of the data.